Ongkara Pranava Sebuah Konsep Ritual Dalam Diri - Ni Made Evi Kurnia Dewi (Jayapangus Press, 2021)
This paper contains about Ongkara Pranava, the concept of ritual within the self. Ongkara Pranava is a sacred mantra that many Hindus chant in the archipelago, and even in the world. Another name for Ongkara is Pranava, which means